Posterolateral Corner Injury Associated with a Schatzker Type 2 Tibial Plateau Fracture - Boris A. Zelle; James R. Heaberlin; Matthew C. Murray (Case Reports in Orthopedics)
Isolated posterolateral corner (PLC) injuries are rarely seen with tibial plateau fractures and can be missed during the initial assessment. The objective of this paper is to present a case of a Schatzker type 2 tibial plateau fracture with associated isolated PLC injury and give a discussion on physical exam, diagnostic studies, and treatment options. A twenty-five-year-old female sustained a concomitant Schatzker type 2 fracture and PLC injury. Magnetic Resonance Imaging showed an isolated PLC disruption. Open reduction-internal fixation was performed with subsequent PLC repair. At sixteen months postoperatively, the patient had full range of motion and strength of her knee and no signs of laxity. This case emphasizes the importance of physical exam and appropriate imaging modalities in order to diagnose and treat this significant injury in a prompt fashion. In this case, surgical fracture fixation and subsequent repair of the PLC provided a good clinical outcome.